Libel And Its Relation To Freedom Of Speech: A Comparative Study Between Malaysian Laws And The Islamic Legal Principles - Hasbollah Bin Mat Saad
Freedom of speech is fundamental towards the founding of a democratic country as distinctly expressed in Article 10(l)(a) of the Federal Constitution. However, there are restrictions to this right and Worn. Article 10(2)(a) of the Federal Constitution exempts or excludes defamation actions from this right by passing the Defamation Act 1957 to control and ensure this right and M o m of speech are exercised in accordance with law. This research concentrates only on one element of defamation under the Defamation Act 1957 and Penal Code (Act 574); libel. Therefore, this thesis will focus on the extent of the rights and M o m of speech, and how elements of libel plays a significant role in determining the restrictions of freedom of speech. The objectives of conducting this research are to examine the scope, concept and development of libel, explore the possible harmonisation, and establish recommendations that could be used to enhance the libel law. This thesis look into the matter from the Malaysian law and the Islamic legal perspectives. Comparative legal research and qualitative methods will be applied in this thesis based on the legal materials; law reports, legal commentaries, judicial decisions, Quranic verses, As-Sunnah, and opinions derived from Muslim scholars. The general observations is that, there are similarities and differences in Ilk1 laws according to the Malaysian laws and the Islamic legal principles which can be blended to form an effective Malaysian libel laws. It can strengthen the countermeasure against more complicated libel actions and at the same time to balance and integrate the relationship between libel laws and freedom of speech, and this may be implemented through the harmonisation processes .